Community water scarcity practices in Ngwezi River Basin, Southern Zambia - Wankie, Richman; Chisola, Moses; Nyanga, Progress; Sichigabula, Henry (Frontiers in Water, 2025)
Extreme droughts in Southern Zambia have intensified water scarcity, contributing to livelihood disruption, social tensions, and adaptive migration across the Ngwezi River Basin. Although dams and boreholes have been developed through climate-resilience programmes, uncertainty remains regarding the sustainability of these interventions and their integration with community-based governance systems. This study examined the interaction between local water-management practices and formal governance structures using the Integrated Water Resources Management (IWRM) framework. A mixed-methods approach was employed, combining household surveys, focus group discussions, and key-informant interviews across upstream, middle-reach, and downstream communities. Quantitative data were analysed using chi-square tests, while qualitative data were thematically analysed to capture institutional, cultural, and hydrological influences on adaptation. The results reveal significant spatial variation in water-management practices across the basin (p < 0.05). Communities employ diverse strategies, including rainwater harvesting, soil-moisture conservation, crop diversification, and social water-sharing arrangements, reflecting strong local adaptive capacity but limited engagement with formal institutions, particularly the Water Resources Management Authority (WARMA). Participants further indicated that state- and NGO-led interventions often overlook customary governance structures and reinforce inequities in water access. The study concludes that strengthening water security in the Ngwezi River Basin requires hybrid governance arrangements that integrate local ecological knowledge and customary authority into formal IWRM mechanisms through inclusive decision-making and co-management, thereby enhancing resilience, equity, and the long-term sustainability of water resources in Zambia’s semi-arid regions.